Turnaround Strategy of the Subscription Television Industry in Indonesia - Abdillah, Willy; Usman, Berto; Hasworini, Fidela (International Research Journal of Business Studies, 2022)
This study aims to identify the PESTEL and Porter’s 5-Forces analysis while identifying the turnaround process of TV provider subscription after a decline in firm performance. The case of this study is MSKY Vision Enterprise, which employs a qualitative descriptive approach using the conceptual framework of PESTEL analysis, Porter’s Five forces, and turnaround strategy developed by Hoffman in 1989 in analyzing the condition of a decline in firm performance and an appropriate turnaround strategy. The study is initiated by firstly investigating financial distress using a Multiple Discriminant Analysis (MDA) developed by Altman and Hotchkiss (2006). Furthermore, an analysis of the company’s external and internal factors is conducted to determine the causes of performance decline, threats, and opportunities in the pay television industry in Indonesia. Next, a turnover strategy proposition analysis is proposed to identify the strategic and operational actions taken to overcome the decline in performance.